ANALYZING STUDENTS’ READING ABILITY TO COMPREHEND TEXTS AT GRADE V OF GROUP I OF ELEMENTARY SCHOOLS AT DISTRICTS TAMPAN PEKANBARU - Azri Muzhar (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This was a descriptive quantitative study. The purpose of this study was to determine the reading comprehension ability of fifth grade students of Group I of Elementary Schools, Kecamatan Tampan, Pekanbaru. The data were collected through a test in the form of multiple choice questions, totaling 50 items. The validity of the research was performed by experts. The samples in this study were 343 students coming from 5 schools, namely SDN 37 Pekanbaru, SDN 147 Pekanbaru, SDN 192 Pekanbaru, SDN 188 Pekanbaru, and SDI Brilliant Pekanbaru. The results showed that the average indicator of understanding the meaning of the word was 61.34 with sufficient category, the indicator for understanding the content in the paragraph was 61.72 with sufficient category, the indicator of determining the main idea was 64.72 with sufficient category, the indicator in the correct order of sentences was 63.09 with sufficient category, and the indicator of concluding the reading text was 62.36 with enough category.